Analisis Introduksi Trichoderma harzianum dan Pupuk Bokhasi Terhadap Perkembangan Sclerotium rolfsii pada Tanaman Kedelai - Susanna Susanna; M. Ilyas Abubakar; Mulizar Mulizar (Fakultas Pertanian, Universitas Syiah Kuala, 2007)
Analysis Introduction of Trichoderma harzianum and Bokhasi Fertilizer to Sclerotium rolfsii on Soybean PlantationABSTRACT. The activity of the antagonist agent T. harzianum in reduction the development of S. rolfsii on the soybean plantation could be simultanted by application bokhasi fertilizer. The aim of the experiment was to study the effect og introducting of biological agent T. harzianum and application bokhasi fertilizer to S. rolfsii development on the soybean plantation. The study was carried out in BLP Ulee Kareng and experiment garden of Agriculture Faculty, Syiah Kuala University, using a Factorial Completely Randomized Design with nine treatment and three replication. Variable observed by incubation periods, pre emergence damping off, post emergence damping off, and the length of the lesion colour basic stem. The result showed that the effect of the application of the combination between biocontrol agent with bokhasi fertilizer can be reducing S. rolfsii development on the soybean. The best treatment to control sclerotium wilt were the combination between T. harzianum 16 g/polybag with bokhasi fertilizer 80 g/polybag.